KAJIAN KAPASITAS TAMPUNGAN AIR EMBUNG BOLON PARANGINAN SELATAN KECAMATAN MUARA KABUPATEN TAPANULI UTARA - Zevri, Asril (JURNAL TEKNIK SIPIL, 2024)
this study aims to analyze the volume of the storage capacity of the Bolon Paranginan Selatan storage as a solution to meet the water needs of both irrigation and raw water due to the increase in population and the need for food in Muara District, North Tapanuli Regency. The study was conducted in the Bolon Paranginan Selatan storage with the water source coming from rainfall that flows within the catchment area of the storage. The method approach is carried out quantitatively based on the simulation of the storage volume capacity between inflow and outflow. The research methodology is carried out by analyzing monthly rainfall, monthly dependable discharge with a probability of 80%, irrigation water demand discharge, population projections, raw water demand discharge, and numerical analytical simulation of storage capacity. The results showed the large volume of storage capacity of the Bolon Paranginan Selatan is 12.034,71 m3 with the height of 3 m from the bottom of the storage for the utilization of raw water needs of 6768 people and the potential area of irrigation area reaching 30,671 Ha with an increase in cropping patterns to twice the planting period.